Transformasi SDM Dalam Menghadapi Tantangan Revolusi 4.0 di Sektor Kepelabuhan - Himawan Aditya Pratama; Heni Dwi Iryanti (Sekolah Tinggi Maritim Yogyakarta, 2020)
At present Indonesia is facing the era of the 4th Industrial Revolution or the Industrial Revolution 4.0. Therefore the 4.0 industrial revolution in the port sector is a good thing to go to smart ports and smart supply chains. Along with the 4.0 industrial revolution and digital technology, business competition and development that originally relied on the use of natural resources will shift to the mastery of information technology and workforce competencies. This is where the importance of HR investment. The era of the industrial revolution 4.0 opened the opportunity for human resources (HR) in the manufacturing sector to have expertise in accordance with the latest technological developments. For this reason, an up-skilling or reskilling workforce program is needed based on the current needs of the industrial world.